Peristaltic transport of Johnson–Segalman fluid in a curved channel with compliant walls - Hina, Sadia; Hayat, Tasawar; Asghar, Saleem (Nonlinear Analysis: Modelling and Control, 2012)
The present investigation deals with the peristaltic flow of an incompressible Johnson–Segalman fluid in a curved channel. Effects of the channel wall properties are taken into account. The associated equations for peristaltic flow in a curved channel are modeled. Mathematical analysis is simplified under long wavelength and low Reynolds number assumptions. The solution expressions are established for small Weissenberg number. Effects of several embedded parameters on the flow quantities are discussed.